Genotoxicity evaluation of two metallic-insecticides using Allium cepa and Tradescantia pallida: A new alternative against leaf-cutting ants - de Souza, Raphael Bastão [UNESP]; de Souza, Cleiton Pereira [UNESP]; Bueno, Odair Correa [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Elsevier, 2017)
In order to combat leaf-cutting ants, the pesticide sulfluramid used to be the most widely utilized active ingredient. However, its use was banned in 2009 by the Stockholm Convention, although some countries were allowed to continue using it. As an effective alternative to its replacement, researchers developed a metallic-insecticide system, which is a natural product linked to metal complexes. Thus, the aim of this study was to evaluate the ability of these new metallic-insecticides in change the genetic material of non-target organisms. The tests were performed utilizing chromosomal aberrations and micronucleus tests in the Allium cepa test system and the Trad-MCN test in Tradescantia pallida. To better understand the results, one of the components of the formula, 5-methyl-phenanthroline, was also analyzed according to the same parameters. To A. cepa, the results showed that one of the metallic insecticides induced cytotoxicity and genotoxicity at different concentrations, while the other metallic-insecticide showed chromosomal instability only at the highest concentration. The analysis of 5-methyl-phenanthroline revealed that it can be related with the positive results, since genotoxic effects were induced. In the Trad-MCN test, none of the metallic-insecticides showed genotoxic activity, although one of them induced more micronucleus formation.
Keywords: Ants; Chromosomal instability; Micronucleus; Natural formicide